Activating responsible citizens: depoliticized environmentalism in hegemonic neoliberalism. Issue 3 (2nd April 2020) - Maxton-Lee, Bernice
ABSTRACT: In an era of apparent "post-democracy", political participation is challenged on multiple levels. On the one hand, traditional understandings of democratic participation appear to be out of sync with current socio-political realities. The rise of multinational corporations has introduced a strong and dominant influence into the balance of politics, with implications for the way social, economic, and political issues are prioritized, represented, and understood. At the same time, demands from citizens for self-determination are growing. Responding to multiple inputs, new forms of participation are rising, which appear to reconcile complex demands and problems. This article explores the role of eco-consumerism in this post-democratic setting, asking how and why eco-consumerism is understood as political participation. It analyses levels of autonomy for citizens within eco-consumerism, questions the extent to which responsibility is applied to consumers for solving complex socio-ecological problems, and debates charges that eco-consumerism depoliticizes socio-political issues to economic transactions.